P79 Preparing for life on-call: developing on-call simulation training for final year medical students. (3rd November 2019) - Cripps, Frederick; Roberts, Nicholas; Lau, Dawn
Abstract : Background: The first on-call shift is a scary proposition for a new foundation doctor, and is a task for which many feel unprepared. Simulation training is increasingly used to help prepare final year medical students for working on-call, but often consists of discrete stations instead of a resembling a continuous on-call shift (Wald et al. 2016). This method allows students to practice medical management of acutely unwell patients, but may not provide adequate training in necessary non-technical skills for working on-call such as organisation, prioritisation, responding to pagers, and working under time pressure. We set out to develop an effective simulated on-call training session, which would incorporate these non-technical skills and help prepare medical students for working on call. Summary of work: 5 simulated on-call sessions were run with a total of 18 final year Cardiff medical students. At the start each student received a pager and a brief handover including 2 outstanding tasks. During the session students were paged with details of new tasks to complete, and could receive multiple requests in quick succession requiring prioritisation of tasks. In total each student had to complete 10 simulated tasks situated in different hospital wards at University Hospital of Wales. At the end of the session the students were individually debriefed on their performance, and quantitative and qualitative feedback was collected. Summary of results: On a scale of 1–10 all 18 students rated the usefulness of the session as 10. After the simulation the students reported a significantly higher confidence in: responding to pagers (p<0.001), prioritising clinical tasks (p<0.001) and managing common on call situations (p<0.001), when compared to their confidence before the simulation. The students identified these key factors that contributed to the usefulness of the session: practising prioritising tasks, practising routine F1 tasks, situating the tasks on hospital wards, and use of real pagers. Discussion and conclusions: The students gave very positive feedback regarding the simulation and found the inclusion of non-technical skills to be the most useful aspect. By designing the simulation as a continuous experience we were able to incorporate aspects of working on-call such as task prioritisation which the students had not previously been exposed to and which they valued highly. Recommendations: It is important that on-call training fully incorporates non-technical skills for it to be effective. On-call simulation training should be designed as a continuous session instead of discrete simulated tasks. References: Wald D, Peet A, Cripe J, Kinloch M. (2016). A simulated Night on Call experience for graduating medical students. MedEdPORTAL ; 12:10483. https://doi.org/10.15766/mep_2374-8265.10483